Leave no one behind : time for specifics on the Sustainable Development Goals - Kharas, Homi J., 1954-; McArthur, John W.; Ohno, Izumi (Brookings Institution Press, 2020)
"The ambitious 15-year agenda known as the Sustainable Development Goals, adopted in 2015 by all members of the United Nations, contains a pledge that "no one will be left behind." This book aims to translate that bold global commitment into an action-oriented mindset, focused on supporting specific people in specific places who are facing specific problems. In this volume, experts from Japan, the United States, and other countries address a range of challenges faced by people across the globe, including women and girls, smallholder farmers, migrants, and those living in extreme poverty. These are many of the people whose lives are at the heart of the aspirations embedded in the 17 Sustainable Development Goals. They are the people most in need of such essentials as health care, quality education, decent work, affordable energy, and a clean environment. This book is the result of a collaboration between the Japan International Cooperation Research Institute and the Global Economy and Development program at Brookings. It offers practical ideas for transforming "leave no one behind" from a slogan into effective actions which, if implemented, will make it possible to reach the Sustainable Development Goals by 2030. In addition to policymakers in the field of sustainable development, this book will be of interest to academics, activists, and leaders of international organizations and civil society groups who work every day to promote inclusive economic and social progress"--